1988
DOI: 10.1007/bf00130545
|View full text |Cite
|
Sign up to set email alerts
|

Influences on women's entry into male-dominated occupations

Abstract: This article focuses on women's entry into male-dominated occupations in the United States. It looks at the impact of Title IX and related legislation which opened access to colleges and universities to women and examines the effect/s of initial or pre-enrollment student characteristics, organizational attributes of the college of university, student performance and experiences in higher education and the attributes of employing organizations on women's entry into male-dominated occupations. The article conclu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
5
0

Year Published

1988
1988
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 22 publications
0
5
0
Order By: Relevance
“…A large body of research documents the cognitive and psychosocial changes students experience during college as a result of the effects of institutions’ structural characteristics and distinct cultural contexts. These changes extend to shifts in liberal social values, gender role attitudes, and gendered career orientations (Ethington, Smart, and Pascarella 1988; Sax 2008; Sax and Bryant 2006). Furthermore, nearly half of college students change their major at least once before graduation (Sklar 2014), suggesting the possibility that students’ experiences in specific college environments may influence their choice of major.…”
mentioning
confidence: 99%
“…A large body of research documents the cognitive and psychosocial changes students experience during college as a result of the effects of institutions’ structural characteristics and distinct cultural contexts. These changes extend to shifts in liberal social values, gender role attitudes, and gendered career orientations (Ethington, Smart, and Pascarella 1988; Sax 2008; Sax and Bryant 2006). Furthermore, nearly half of college students change their major at least once before graduation (Sklar 2014), suggesting the possibility that students’ experiences in specific college environments may influence their choice of major.…”
mentioning
confidence: 99%
“…Weidman (1979) found that holding a leadership position in student government or other organizations did not have a direct effect on career choice. However, other studies (Braxton et al 1990;Ethington, Smart, and Pascarella 1988) suggest that extracurricular activities may positively affect career mobility.…”
Section: Practical Competencementioning
confidence: 95%
“…Educationally purposeful out-of-class experiences such as voluntarism, community service, and holding office in student government or other organizations positively contribute to leadership development, decisionmaking skills, and feelings of personal competence (Ethington, Smart, and Pascarella 1988;Evanoski 1988;Kuh 1995;. For example, leadership experiences (e.g., student government or fraternity officer, peer advisor) accounted for almost one-quarter of all gains reported by seniors in this area (Kuh 1995).…”
Section: Practical Competencementioning
confidence: 99%
“…A few studies paid attention to educational and training structure and how different kinds of academic training might lead females into different labor market fields (Duncan and Hoffman 1979;Ethington et al 1988;Randor et al 1982).…”
Section: Introductionmentioning
confidence: 99%
“…Although there is a rich body of literature that looks at the impact of social and human capital variables on the earnings of women (Blau andKahn 1997, 2000;Darity and Mason 1998;Desai and Waite 1991;Duncan and Hoffman 1979;Ethington 1988;Ferber and Spaeth 1984;Fleisher and Rhodes, 1979;Heckman 1978;Mason 1999;Randor et al 1982;Sanborn 1964; to name a few), to this author's knowledge, few studies address the roles of factors such as age, marital status, number of children, and education in determining the probability of female presence in a traditionally male-dominated occupation. The author defines an occupation to be traditionally maledominated where at least 75% of the total workforce is male.…”
Section: Introductionmentioning
confidence: 99%